Impaired fasting glucose, oxidative distress, and cognitive impairment. Is this the starting point on DBT cognitive decline? - Canal, María Pilar; Nini, Karen Agustina; Baez, Maria Verónica (Frontiers in Aging Neuroscience, 2022)
Different studies performed in human patients, animal models, and in vitro in cell cultures, show a correlation between type 2 diabetes (DBT2) and certain neurodegenerative pathologies. Also, it was proposed that increased inflammation and-or oxidative stress are a possible cause for DBT2-accelerated cognitive decline. The onset of DBT2 is characterized by an increase in blood glucose levels due to (an inability of the body's cells to use insulin properly) called impaired fasting glucose (IFG). Genetic and/or molecular causes of IFG have not yet been established, but metabolic syndrome, obesity, unbalanced diets, and sedentary lifestyle would be responsible, at least in part, for the multiplication in number of this disease. It has been proposed that hyperglycemia itself causes an imbalance in redox state and could compromise BBB causing neurodegeneration. For this reason, we propose, in this review, evaluate the available data about redox state and neurocognitive studies during IFG period.